Pengaruh E-learning terhadap Minat Belajar Siswa Kelas X OTKP di SMKN 2 Buduran Sidoarjo - Wakhidatur Rokhmani Citra Rivai; Durinta Puspasari (Edunusa: Journal of Economics and Business Education, 2022)
The purpose of the research was to analyze the impact of e-learning on student interest in studying in class X OTKP at SMKN 2 Buduran Sidoarjo. This study is a type of study with a quantitative approach. The population in this research were all students of class X OTKP totaling 75 students. The data collection method in this research were closed questionnaires and unstructured interviews. Instrument testing includes instrument validity and instrument reliability. While the data analysis techniques used in this study are: the classical assumption test which includes the normality test and heteroscedasticity test, and hypothesis testing using a simple linear regression test. The results showed that the results of simple linear regression analysis for a significance value of 0.000. Which is the significance value is smaller or < 0.05. While the value of the t count is 10,062 and the value of the t table is 1,995. This means t count > t table or 10,062 > 1,995, it can be concluded that e-learning has a significant effect on students' interest in learning.